Scaling a Multi-dimensional Organization Horizontally - Bigley, Joel (Archives of Business Research, 2020)
Customers of multinational enterprises (MNEs) exist almost everywhere. Cross border B2C e-commerce is expected to double by 2022 according to Forrester Research. How do MNE’s efficiently leverage their product portfolios across geographic markets? This is called horizontalization. Synergies exist in terms of resources needed in these products due to relatedness between them. Economies of scale can be exploited to reduce costs of needed resources. In this case study an MNE utilized a multidimensional organization design to reach customers in many parts of the world. The author presents findings from this case and ultimately extracts nineteen propositions to guide support function synergies. Absent these measures, risk of revenue loss is enhanced significantly.